Synthesis, Characterization, Cytotoxicity, And Antimicrobial Activity Of Azobenzene-Imidazolium Ionic Liquid Crystals - Funmilayo, Babamale Halimah (2023)
Four new series of azobenzene-imidazolium salts were synthesized by azo coupling, followed by alkylation and subsequent quaternization of N-alkylated imidazoles of various chain length with azobenzenes to afford the non-fluorinated (9a-9e), difluorinated (10a-10e) and tetrafluorinated (11a-11e, 12a-12j) salts. The purity of the compounds was confirmed by CHN elemental analysis and their structures were elucidated using the FTIR, 1D and 2D NMR spectroscopies. The liquid crystalline (LC) properties of the salts were studied using the DSC and POM. In vitro cytotoxicity was explored using the MTT assay and their antimicrobial activities were investigated using the disc diffusion method. Smectic A (SmA) phase was observed in almost all compounds.